Prevalence of Some Genetic Risk Factors for Nicotine Dependence in Ukraine. (20th October 2019) - Bashynska, Vitalina; Koliada, Alexander; Murlanova, Kateryna; Zahorodnia, Oksana; Borysovych, Yuliia; Moseiko, Vladyslav; Lushchak, Oleh; Vaiserman, Alexander
Abstract : Tobacco smoking is known to be a strong risk factor for developing many diseases. The development and severity of smoking dependence results from interaction of environmental and lifestyle factors, psycho-emotional predispositions, and also from genetic susceptibility. In present study, we investigated polymorphic variants in genes contributed to nicotine dependence, as well as to increased impulsivity, known to be an important risk factor for substance use disorders, in Ukraine population. The genotype frequencies at CYP2A6, DNMT3B, DRD2, HTR2A, COMT, BDNF, GABRA2, CHRNA5, and DAT1 polymorphisms were determined in 171 Ukraine residents, and these data were compared with data for several other European populations and main ethnic groups. It has been found that genotype frequencies for all studied loci are in Hardy-Weinberg equilibrium in the Ukrainian population and correspond to the respective frequencies in European populations. These findings suggest a similar impact of these loci on nicotine dependence in Ukraine. Further studies with larger sample sizes are, however, needed to draw firm conclusions about the effect size of these polymorphisms.